نظم المعلومات و علاقتها بفاعلية إتخاذ القرارات لدى الموظفين الاداريين بالجامعة - قبوري، حيزية (university of Eloued جامعة الوادي, 2016)
Abstract: Organizations trying to achieve success in light of the changes that abound in the internal and external environment to her, that success is linked to the extent of drawing the right goals and it depends on the effectiveness of management at the correct decision-making information is and the basis on which the focus of the decisions, and that will provide decision makers with an absolute ability to make the decision as a proper and thoughtful. And therefore we have to ask the next question is whether there is a statistically significant correlation between the characteristics of information systems and the effectiveness of decision-making? This study aims to find out the relationship between information systems and the effectiveness of decision-making at the university administrative staff, and how the decision is made in the institution under study Been relying on a descriptive approach and the application of the field study on intentional sample consisting of 31 single, and we used a questionnaire as a tool to collect data, and then prove hypotheses through the SPSS program, the study concluded the following results: -No statistically significant correlation between the information systems and the quality of decision Properties. -There is no statistically significant correlation between the information systems and applicability properties. -There is no statistically significant correlation between the information systems and adjustability properties. -No statistically significant correlation between the information systems and the characteristics of effective decision-making
دراسة ميدانية في كلية العلوم الاجتماعية و الانسانية بجامعة الوادي
مذكرة ماستر علوم إجتماعية تخصص تنظيم وعمل
Keywords: نظم المعلومات، إتخاذ القرار; Systèmes d'information, prise de décision; Information Systems, Decision Making